Review of Scientific Research on Informal Learning Using Information and Communication Technologies in Education: A Bibliometric Analysis - Yong-Chung, Felipe (2023)
This article aims to make a bibliometric review, through the Web of Science (WoS) database, on informal learning. For this, a systematic search of research articles related to the subject of study is made, applying the consolidated meta-analytic approach theory (TEMAC). The study finds that the country with the most research is the United States with 38.1% of publications among the 10 most productive countries. Likewise, the use of augmented reality and virtual simulation games are identified as the digital technologies most associated in recent years with informal learning, with positive results in student learning and performance.